2013
DOI: 10.5296/jee.v4i2.4961
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of AVI and DRASTIC Methods for Groundwater Vulnerability Mapping

Abstract: The Densu River Basin is one of the important basins in Ghana. A large number of residents in this basin are dependent on groundwater for their livelihood. However, with the growing population, urbanization and impact of climate change, it is imperative to develop ways to protect and manage the limited groundwater resource that is supporting the communities. As a result, this paper assessed the groundwater vulnerability by comparing two methodsthe Depth to water, net Recharge, Aquifer media, Soil media, Topogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
(15 reference statements)
1
5
0
1
Order By: Relevance
“…AVI and DRASTIC are both suitable for porous aquifers. The limitation of the AVI method, revealed in previous studies [19,21] and confirmed by this study, consists of low differentiations of areas at different degrees of vulnerability, especially in alluvial aquifers as well as with a prevalence of the highest class of vulnerability. Some authors argue that the degree of susceptibility/vulnerability is exaggerated by AVI [24].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…AVI and DRASTIC are both suitable for porous aquifers. The limitation of the AVI method, revealed in previous studies [19,21] and confirmed by this study, consists of low differentiations of areas at different degrees of vulnerability, especially in alluvial aquifers as well as with a prevalence of the highest class of vulnerability. Some authors argue that the degree of susceptibility/vulnerability is exaggerated by AVI [24].…”
Section: Discussionsupporting
confidence: 65%
“…The AVI (Aquifer Vulnerability Index) method [14] was developed a few years after DRASTIC, utilizes the potential offered by GIS systems, and has also been widely used because it has the advantage of using only two physical parameters. Comparisons between these two methods [10,[15][16][17][18][19][20] demonstrate that both AVI and DRASTIC are suitable for predicting the pollution potential for porous aquifers. The AVI method tends towards higher vulnerability outcomes than DRASTIC, especially in shallow aquifers [21].…”
Section: Introductionmentioning
confidence: 99%
“…To com pare maps of in trin sic ground wa ter vul ner a bil ity, each vul ner a bil ity method was di vided into 5 classes with prescribed re la tion ships (Ta ble 2). The in fil tra tion travel-time classes are dif fer ently di vided in lit er a ture: from 1 week to 1 year (Debernardi et al, 2008); from 0 years to >10,000 years (Anornu and Kabo-bah, 2013); from 0 years to >30 years (Krogulec, 2006); from <5 years to >100 years (Witczak et al, 2007); from <1 year to > 25 years (Schwartz, 2006). If real val ues are given in the text, such as years, re sults re main com pa ra ble.…”
Section: Methodsmentioning
confidence: 99%
“…Freshwater, a critical and indispensable resource for life, faces escalating threats due to the growing populations and rapid industrialization, particularly in regions rich in petroleum resources, such as the Niger Delta in Nigeria [1,2]. The intricate interplay of natural processes and human activities significantly influences the quality of water in these areas [3]. When untouched by human influence, water quality is shaped by natural phenomena like weathering, evapo-transpiration, and biological interactions, resulting in the presence of various dissolved substances and particulate matter, essential for the health of aquatic ecosystems [4].…”
Section: Introductionmentioning
confidence: 99%